Streamlining Resiliency: Regulatory Considerations in Permitting Small Scale Living Shorelines - Thomas T. Ankersen; Alexandra Barshel; Valerie Chesnut (EDIS)
Living shorelines offer a valuable and environmentally friendly means of stabilizing shorelines while restoring and enhancing estuarine habitats. Because living shorelines are considered environmentally beneficial, several agencies have coordinated efforts to reduce the regulatory burden required to construct them. This 8-page fact sheet written by Thomas T. Ankersen, Alexandra Barshel, and Valerie Chesnut and published by the Florida Sea Grant College Program, UF/IFAS Extension, describes how to ensure that a living shoreline project will be successful and not run into any permitting difficulties. http://edis.ifas.ufl.edu/sg155